Structural basis of DNA packaging by a ring-type ATPase from an archetypal viral system. Issue 15 (10th August 2022) - Fung, Herman K H; Grimes, Shelley; Huet, Alexis; Duda, Robert L; Chechik, Maria; Gault, Joseph; Robinson, Carol V; Hendrix, Roger W; Jardine, Paul J; Conway, James F; Baumann, Christoph G; Antson, Alfred A
Abstract: Many essential cellular processes rely on substrate rotation or translocation by a multi-subunit, ring-type NTPase. A large number of double-stranded DNA viruses, including tailed bacteriophages and herpes viruses, use a homomeric ring ATPase to processively translocate viral genomic DNA into procapsids during assembly. Our current understanding of viral DNA packaging comes from three archetypal bacteriophage systems: cos, pac and phi29. Detailed mechanistic understanding exists for pac and phi29, but not for cos . Here, we reconstituted in vitro a cos packaging system based on bacteriophage HK97 and provided a detailed biochemical and structural description. We used a photobleaching-based, single-molecule assay to determine the stoichiometry of the DNA-translocating ATPase large terminase. Crystal structures of the large terminase and DNA-recruiting small terminase, a first for a biochemically defined  cos system, reveal mechanistic similarities between cos and pac systems. At the same time, mutational and biochemical analyses indicate a new regulatory mechanism for ATPase multimerization and coordination in the HK97 system. This work therefore establishes a framework for studying the evolutionary relationships between ATP-dependent DNA translocation machineries in double-stranded DNA viruses.